Monetary Relationships among Secondary School Students in Minority Schools - Mihailova, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The issue becomes especially important for young people, especially secondary school students, their attitudes toward money, to make predictions about people's socio-economic behavior in the future. The current high school students after several years will be active players of many socio-economic processes, therefore research of their current attitudes towards money - may be particularly interesting, instructive, and enable adjustments to eliminate the potential problems of the monetary behavior in the future. Such studies can give students the necessary knowledge of the behavior of money that will be contribution to the practice of psychological counseling. Currently, the monetary aspect of the relationship of psychological research in both empirical and theoretical perspective is global, but hardly done in Latvia. Therefore, this pilot study is an attempt to develop an insight into this topic in Latvia. The paper examines the secondary monetary relationship in minority school in Riga (in Latviaa), and the results are compared with similar research data in Russia.